PTH-019 Palliative stenting for inoperable oesophageal cancer: results of a national survey of health professionals. (22nd June 2015) - Driver, R; Kite, S; Radhakrishna, G; Wright, P; Hull, M; Everett, S
Abstract : Introduction: In recent years, the role of oesophageal stenting for malignant dysphagia has evolved alongside other palliative treatments for oesophageal cancer. Management has become increasingly multidisciplinary and different considerations affect decisions about the timing and appropriateness of palliative stenting. We sought to assess the current UK practice of palliative stenting in oesophageal cancer. We assessed which specialties perform the procedure, which technique is used, the use of anti-reflux stents and investigated how different clinicians involved in the care of these patients would recommend managing dysphagia in different clinical scenarios. Method: An online survey was sent out to the professional bodies of the members of the Upper GI MDT. Opinions of health professionals including gastroenterologists, oncologists, palliative care physicians, surgeons, radiologists and nurse specialists on the benefits and discomfort associated with the procedure were evaluated. Four clinical scenarios were used to evaluate opinions on maintaining nutrition prior to stenting, stenting in end-of-life care and the role of the MDT. Results: The survey received 239 respondents, including 92 individuals (39%) who regularly insert oesophageal stents ('stenters'). 63% of stents are inserted via endoscopy with fluoroscopic guidance, 20% with fluoroscopic guidance alone and 17% with endoscopy alone. 74% of responders never use anti-reflux devices, irrespective of the involvement of the gastro-oesophageal junction. 92% of respondents considered that stenting improved long-term dysphagia. Among the stenters, 20% considered that patients experience significant discomfort with some distress during the procedure (compared with 43% of non-stenters) and 16% during the days post-procedure (compared with 55% of non-stenters). 92% of stenters consider that the procedure improves quality of life in the 4 weeks post-procedure, compared with 78% of non-stenters. The clinical scenarios revealed that 15% of respondents would recommend stenting in end of life care in a patient who was managing a semi-solid diet, whereas 44% would consider stenting only if swallowing deteriorated subsequently. In complete dysphagia, 40% of respondents would recommend awaiting MDT discussion prior to oesophageal stent placement. Conclusion: Health professionals' perceptions of patient discomfort and improvement in quality of life are associated with the individuals' experience of performing oesophageal stent insertion. These perceptions may influence decisions about timing and indication for oesophageal stenting. Care should be taken to acknowledge this, alongside the variation in opinion among clinicians over optimal management in different scenarios. Disclosure of interest: None Declared.